Teaching respectful maternity care using an intellectual partnership model in Tanzania. (May 2018) - Wilson-Mitchell, Karline; Robinson, Jamie; Sharpe, Mary
Abstract: Objective: to develop and deliver a two-day Respectful Maternity Care workshop for midwives using Intellectual Partnership Model principles Setting: rural Tanzania Background: respectful Maternity Care is an objective, measurable indicator of quality maternal newborn care Interventions: using the Intellectual Partnership Model, educators facilitated cocreation of solutions alongside learners for complex ethical and logistic problems in the workplace Findings: the mean scores on a 10-item multiple choice test increased by 20% on average following completion of the interventions; however 2-year certificate learners were less prepared for critical thinking work and social innovations than those midwives who had 3 or 4 year formal training Key conclusions: the implementation of the Intellectual Partnership Model revealed that midwife learners were creative, innovative, context specific in their social innovation creations related to Respectful Maternity Care when supported by respectful facilitators. Implications for practice: the Intellectual Partnership Model should be considered along with problem-based learning in the Global South, for pre and post-service education. Highlights: Intellectual Partnership Models can be used to teach Respectful Maternity Care to midwives. Knowledge content test scores improved by 20%. Participants produced social innovations in a complex, low-resource environment. Participants reported feelings of increased agency and empowerment.